Conservation of some endemic species of the genera leucozonella and archaica and measures for their protection - Makhmudjonov Zafarjon Murodjon ugli; Khudoyberdiyeva Sevinch Muzaffar qizi; Rahmonova Zilola Mirzatilla qizi; Haidarov Islombek Mamat ugli; Chutanov Bakhrom Egamberdievich; Khudoyberdiyev Firdavs Koʻchim ugli (Zien Journals, 2024)
The article examines the protection and measures for the protection of Leucozonella corona and Archaica eleorica. Leucozonella corona Schileyko et Rymzhanov, 2010 is a weak, naturally rare, locally distributed, endemic species. It is distributed in certain areas in the Chotkal and Kurama m ountain ranges. Archaica eleorika Schileyko et Pazilov, 2003-weak, naturally rare, endemic species. Distributed in the hilly regions of Shahrisabz district, Kashkadarya region.
Keywords: Endem; biology; limiting factor; protection